Open Verification Methodology Cookbook - Glasser, Mark.; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Glasser, Open Verification Methodology Cookbook Functional verification is an art as much as a science. It requires not only creativity and cunning, but also a clear methodology to approach the problem. The Open Verification Methodology (OVM) is a leading-edge methodology for verifying designs at multiple levels of abstraction. It brings together ideas from electrical, systems, and software engineering to provide a complete methodology for verifying large scale System-on-Chip (SoC) designs. OVM defines an approach for developing testbench architectures so they are modular, configurable, and reusable. This book is designed to help both novice and experienced verification engineers master the OVM through extensive examples. It describes basic verification principles and explains the essentials of transaction-level modeling (TLM). It leads readers from a simple connection of a producer and a consumer through complete self-checking testbenches. It explains construction techniques for building configurable, reusable testbench components and how to use TLM to communicate between them. Elements such as agents and sequences are explained in detail. Offers a must-have reference to the Open Verification Methodology (OVM); Enables an OVM novice to build production-quality testbenches; Focuses on developing reusable testbench elements; Provides numerous, complete, working examples that illustrate the key points in the text and readers can use as templates in their own work. "Similar in concept to the successful pattern books for programming languages, the OVM Cookbook provides a consistent way to solve verification problems, beyond what naming conventions and a well designed framework can provide. I have found the OVM Cookbook a valuable resource for myself and also as a way to jumpstart the rest of a team on a new methodology. The book provides excellent insights into the use of the OVM methodology and clarifies the terminology used in modern verification environments. " - Warren Stapleton (Senior Fellow, AMD).
Verification Principles -- Fundamentals of Object-Oriented Programming -- Transaction-Level Modeling -- OVM Mechanics -- Testbench Fundamentals -- Reuse -- Complete Testbenches -- Sequences -- Block-to-System -- Coding Conventions.
Keywords: Engineering; Computer-aided engineering; Electronic circuits; Engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design; Electronic books